PERENCANAAN SDM BP ACTIVE MFS PT WES LISENSI BRITISH PETROLEUM – AKR - Whitney, Whitney; Negoro, Dimas Angga; Indradewa, Rhian; Hamdi, Edi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to investigate the human resource planning framework, organizational culture, organizational structure, and HR management practices at PT WES, a petroleum retail company operating in Indonesia. The research methodology employed includes documentation analysis, direct observation, and indepth interviews with senior management and operational staff of the company. The findings indicate that PT WES has successfully developed a meticulously structured HR planning framework, encompassing workforce needs identification, employee development, performance management, and career development. Additionally, the company fosters an adaptive organizational culture, empowering employees to innovate and contribute proactively to the achievement of organizational goals. The simple yet effective organizational structure facilitates communication and coordination among business units, while meticulous HR management practices such as selective recruitment, personalized training, and fair reward systems enhance employee performance. Thus, the conclusion of this research is that PT WES has successfully implemented a holistic and values-oriented HR management strategy to support the long-term growth and success of the company in the petroleum retail industry.